2D graphene-like hierarchically porous carbon nanosheets from a nano-MgO template and ZnCl2 activation: morphology, porosity and supercapacitance performance. Issue 75 (27th July 2016) - Chang, Binbin; Zhang, Shouren; Sun, Li; Yin, Hang; Yang, Baocheng
Abstract : Herein, we developed a facile and cost-efficient route to obtain two-dimensional (2D) graphene-like carbon nanosheets with a well-developed hierarchical pore structure (HPCNS) by using nano-MgO spheres as templates and ZnCl2 chemical activation. Abstract : Herein, we developed a facile and cost-efficient route to obtain two-dimensional (2D) graphene-like carbon nanosheets with a well-developed hierarchical pore structure (HPCNS) by using nano-MgO spheres as templates and ZnCl2 chemical activation. Importantly, the wrinkled degree of the nanosheet and porosity with various micro/mesopore proportions were controlled by tuning the MgO/ZnCl2 ratio. An optimal sample of the HPCNS-1-2 material displayed an ultrathin sheet-like morphology as well as a well-interconnected hierarchical porous structure, a highly accessible surface area (1415.6 m 2 g −1 ) and a large pore volume (1.57 cm 3 g −1 ). As an electrode material for supercapacitor applications, the HPCNS-1-2 electrode presented a high specific capacitance of 332.8 F g −1 at 1 A g −1 and excellent rate capability of above 66% retention even at 30 A g −1 in a 6 M KOH electrolyte. Meanwhile, the HPCNS-1-2 electrode also exhibited a superior energy density of 45.8 W h kg −1 at a power density of 495.3 W kg −1, and also maintained a 23.1 W h kg −1 energy density at an extremely high power density of 11.3 kW kg −1 . In addition, a remarkable long-term cycling stability of about 93.8% capacitance retention was retained after 10 000 cycles at 5 A g −1 in 6 M KOH.